2012
DOI: 10.1039/c2cc31825c
|View full text |Cite
|
Sign up to set email alerts
|

The role of lipophilicity in transmembrane anion transport

Abstract: The transmembrane anion transport activity of a series of synthetic molecules inspired by the structure of tambjamine alkaloids can be tuned by varying the lipophilicity of the receptor, with carriers within a certain log P range performing best.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 28 publications
2
72
1
Order By: Relevance
“…It has often been suggested that ion transport across lipid bilayers is diminished when receptors become too lipophilic to interact with the ions at the lipid-water interphase. 12,24,41,42 In order to obtain an estimate of the lipophilicity of compounds 1–8, experimental retention times on reversed-phase HPLC 43 were determined (Table 3). It is clear that the three inactive transporters are also the receptors with the highest lipophilicity (highest retention time), suggesting that lipophilicity may also contribute to the inactivity of 4, 7 and 8 .…”
Section: Resultsmentioning
confidence: 99%
“…It has often been suggested that ion transport across lipid bilayers is diminished when receptors become too lipophilic to interact with the ions at the lipid-water interphase. 12,24,41,42 In order to obtain an estimate of the lipophilicity of compounds 1–8, experimental retention times on reversed-phase HPLC 43 were determined (Table 3). It is clear that the three inactive transporters are also the receptors with the highest lipophilicity (highest retention time), suggesting that lipophilicity may also contribute to the inactivity of 4, 7 and 8 .…”
Section: Resultsmentioning
confidence: 99%
“…The vesicles were dispersed in an aqueous external solution of sodium nitrate (489 mM NaNO 3 buffered to pH 7.2 with 5 mM sodium phosphate salts). 26 The most active compounds in this series lie either in or just outside this range. Receptors 1-6 were loaded at an appropriate molar percentage relative to the moles of lipid as a DMSO solution at 0 s and the resulting chloride efflux from the vesicles detected by a chloride selective electrode (Accumet).…”
Section: Anion Transport Studies and Hill Analysismentioning
confidence: 99%
“…Figure 2 shows their transport takes longer to begin following the addition of the receptor to the system, giving more of a sigmoidal shape to the curve, receptor 6 also displays a more sigmoidal shape in the Hill plot. This behaviour has previously been noted by Haynes et al (24) which was attributed to the receptors lying outside the optimum lipophilicity values proposed by Saggiomo et al (25) Receptors 5 and 6 possess log P values of 5.1 and 5.44 respectively as calculated by VCC labs, (26) which lie above the optimum lipophilicity values proposed (log P < 4) (25). This would allow the slow start to transport to be rationalised, as delivery through the aqueous external solution is hindered.…”
Section: Resultsmentioning
confidence: 53%